Succession Pattern in Soil Micro-Ecology Under Tobacco (Nicotiana tabacum L.) Continuous Cropping Circumstances in Yunnan Province of Southwest China - Chen, Dan; Zhou, Yujie; Wang, Mei; Mujtaba Munir, Mehr Ahmed; Lian, Jiapan; Yu, Song; Dai, Kuai; Yang, Xiaoe (Frontiers in Microbiology, 2022)
Continuous cropping obstacle (CCO) is a common phenomenon in agricultural production and extremely threatens the sustainable development of agriculture. To clarify the potential keystone factors causing tobacco (Nicotiana tabacum L.) CCO, tobacco plants, topsoil, and rhizosphere soil were sampled from the fields with no, slight, and severe tobacco disease in Dali and Yuxi of Yunnan province in China. The physicochemical properties of topsoil and rhizosphere soil, the phenolic acids (PAs) contents in rhizosphere soil, and elemental contents in topsoil, rhizosphere soil, and tobacco plants were analysed. Microbial diversity in rhizosphere soil was determined by the metagenomic sequencing method. The results showed that soil pH, texture, cation exchange capacity, organic matter, TC, TN, and available K contents showed a significant difference (p < 0.05) in soil physicochemical properties. There was a deficiency of B, K, Mg, Mn contents in soil and/or tobacco plants. The contents of PAs, especially syringic acid in rhizosphere soil, varied significantly among the three sampling groups (p < 0.05). Meanwhile, microbial communities and functional genes changed from beneficial to harmful, showing an intimate correlation with soil pH and syringic acid content. It can be concluded that tobacco CCO could be allocated to the imbalance of soil micro-ecology, which possessed a regional feature at the two sampling sites.